Determinants of Toddler Motor Development: The Role of Maternal Knowledge, Husband Support, Parity, and Socio-Cultural Factors in a Cross-Sectional Study in Makassar, Indonesia - Azrida Machmud; Yusrah Taqiyah (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2026)
Exclusive breastfeeding has benefits for the development and growth of babies. This study aimed to analyze the relationship between maternal knowledge, husband's support, parity, and socio-cultural factors on motor development in toddlers. This research was conducted at the Rappokalling Community Health Center from August to November 2025. This research method was an analytical observational survey with a cross-sectional study approach. The sample in this study consisted of 65 toddlers. The sampling technique used was purposive sampling, a sampling technique based on certain considerations. Data analysis was carried out using the SPSS program, utilizing the Chi-square test. The results of this study indicate that husband's support and socio-cultural factors influence toddler motor development, with a p-value of 0.000, which is less than α = 0.05. Meanwhile, there was no significant relationship between maternal knowledge and maternal parity. The findings highlight the importance of the role of the family, especially the husband and the social environment, in supporting the success of exclusive breastfeeding and motor development in toddlers. Husband and family support are key determinants of successful exclusive breastfeeding practices. The husband's active involvement in seeking lactation information, along with family support in infant stimulation and navigating social norms, significantly impacts parenting patterns and toddler motor development. Therefore, health interventions need to focus on strengthening the family support system to improve the quality of child growth and development